9(-4)-3y=6(y-6)

Simple and best practice solution for 9(-4)-3y=6(y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(-4)-3y=6(y-6) equation:


Simplifying
9(-4) + -3y = 6(y + -6)

Multiply 9 * -4
-36 + -3y = 6(y + -6)

Reorder the terms:
-36 + -3y = 6(-6 + y)
-36 + -3y = (-6 * 6 + y * 6)
-36 + -3y = (-36 + 6y)

Add '36' to each side of the equation.
-36 + 36 + -3y = -36 + 36 + 6y

Combine like terms: -36 + 36 = 0
0 + -3y = -36 + 36 + 6y
-3y = -36 + 36 + 6y

Combine like terms: -36 + 36 = 0
-3y = 0 + 6y
-3y = 6y

Solving
-3y = 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-3y + -6y = 6y + -6y

Combine like terms: -3y + -6y = -9y
-9y = 6y + -6y

Combine like terms: 6y + -6y = 0
-9y = 0

Divide each side by '-9'.
y = 0

Simplifying
y = 0

See similar equations:

| 24+8*2*12= | | 8/(x^2-1)=0 | | -(8n+4)=4n-2(6n+2) | | 5y=7xl | | 5-1m=13 | | -5(1-3x)+3x=-4x+5(5x+2) | | 62+(-5)= | | (31/-4)+(-5/8) | | 4x-4(1+3x)=-(1+5x) | | -5(-8X+2)=26+4X | | 8x+17=22 | | t-3t-7=4t-7 | | 5/6+c=1/3 | | 3(x-5)=7x | | 2x^3+x^2-37x-36=0 | | 5t+12=4-3t | | 3x(x+12)+2x(2x+4)=360 | | x^3+47x-35= | | 2(250-x)+x*4=600 | | -3/b=1 | | x^3+47x-35=0 | | -6=2m | | -3t+8= | | 2X-125=455 | | ((1+2x)/(4))(16) | | 14-4x=9x | | -6(2x-6)+9=-12x+45 | | 7x-9y=-20 | | m/-2=-20 | | f(x)=(x-8)(x+5)(x-2) | | 15+.5(.4)=25+.25(.4) | | 9x-5=9(x-7) |

Equations solver categories